Atom Transfer Radical Polymerization Enabled by Sonochemically Labile Cu-carbonate Species - Wang, Zhenhua; Lorandi, Francesca; Fantin, Marco; Wang, Zongyu; Yan, Jiajun; Wang, Zhanhua; Xia, Hesheng; Matyjaszewski, Krzysztof (ACS macro letters, 2019)
Atom transfer radical polymerization (ATRP) has been previously mediated by ultrasound using a low concentration of copper complex in water (sono-ATRP) or by addition of piezoelectric materials in organic solvents (mechano-ATRP). However, these procedures proceeded slowly and yielded polymers contaminated by new chains initiated by hydroxyl radicals or by residual piezoelectrics. Unexpectedly, in the presence of sodium carbonate, rapid sono-ATRP of methyl acrylate in DMSO was achieved (80% conversion in <2 h) with excellent control of molecular weights and low dispersities (M w/M n < 1.2). The in situ formed CuII/L-CO3 complex in the the presence of ultrasound generated CuI/L species as activators for ATRP and carbonate radical anions. The latter were scavenged by DMSO that was oxidized to dimethyl sulfone. This simple and robust process employs low-intensity ultrasound, air-stable CuII/L catalysts, and carbonate or bicarbonate salts (washing soda or baking soda) to prepare well-defined polyacrylates.